ACCOUNTING STRATEGIES FOR ACHIEVING SUSTAINABILITY: RATIONALIZING COSTS UNDER THE CURRENT ECONOMIC CONDITIONS OF IRAQI COMPANIES: STRATEGI AKUNTANSI UNTUK MENCAPAI KEBERLANJUTAN: RASIONALISASI BIAYA DALAM KONDISI EKONOMI SAAT INI DI PERUSAHAAN-PERUSAHAAN IRAK - ALnujaimi Aws saeed mirdan; MUSLIM BADR JASIM; Mujtaba Ali Hussein (Universitas Muhammadiyah Sidoarjo, 2026)
General Background: Modern management accounting emphasizes the importance of controlling production costs to sustain organizational competitiveness. Specific Background: Companies increasingly rely on cost–value analysis and cost management models to identify inefficient operational expenses and improve financial performance. Knowledge Gap: Empirical research examining cost optimization strategies in Iraqi manufacturing companies remains limited. Aims: This study aims to identify key cost drivers and develop a cost optimization model using empirical data from Baghdad Soft Drinks Company. Results: The Relative Importance Index and factor analysis reveal that direct labor costs represent the dominant component of total production costs, with a relative importance index of 0.989 and an explanatory contribution of 92.3%. Using the cost–volume–profit model, three strategic scenarios were tested: expansion, market penetration, and operational efficiency. The expansion scenario generated the highest profit growth (+55.9%), the efficiency scenario produced moderate growth (+15%), while the penetration strategy caused a substantial decline in profitability (−67.8%). Novelty: The study integrates cost-driver identification with scenario-based cost modeling in an Iraqi industrial context. Implications: These findings provide a practical basis for managerial decision-making and sustainable financial planning through systematic cost optimization. Highlights: Direct labor expenditure emerges as the primary component shaping production cost structure capacity investment produces the largest profitability growth. Operational efficiency strategy yields stable gains with minimal financial risk Keywords: Cost Optimization; Cost Volume Profit Model; Cost Value Analysis; Managerial Accounting Strategy; Production Cost Structure